DUKUNGAN SOSIAL DAN PENGUNGKAPAN DIRI PADA PESERTA DIDIK PROGRAM KESETARAAN PAKET B - LUSSY DWIUTAMI WAHYUNI; RADJITO RADJITO (Journal of Research and Measurement in Psychology, 2017)
This study aims to identify Social Support and Self Disclosure of Paket B students in PKBM Negeri 33 Malaka. This study was conducted using quantitative research, with ex-postfacto research method. Social Support instrument using adaptation from Social Support Scale by Rangga Amarullah and Self Disclosure instrument adaptation of The Jourard Sixty-Item Self Disclosure Questionnaire by Jourard and Lasakow. Procedure sampling technique use saturation sampling. Participants in this research were 38 people who are adolesence of Paket B Students in PKBM Negeri 33 Malaka. Based on the analysis of data, obtained by regression Social Support on Self Disclosure amounted to 13,6% with significance level of 0.023 (p < 0.05). The results showed that there are significant Social Support to Self Disclosure Paket B students in PKBM Negeri 33 Malaka, shown by the regression equation Y = 0,637 + 0,294X which means higher Social Support, higher Self Disclosure, and vice versa.